APPLICATION OF THE VIBRATION-ACOUSTIC METHOD IN DIAGNOSING DRIVE AXLES OF LIGHT VEHICLES - O. Odilov; D. A. Sheraliyev; R. Rapiqjonov (Modern American Journals, 2025)
This article is devoted to the study of vibroacoustic diagnostic methods for identifying defects in the drive axles of wheeled vehicles. The aim of the research is to evaluate the applicability of existing vibration-acoustic diagnostic techniques for assessing the technical condition of these critical components. The vibration-acoustic method allows for non-destructive analysis of the axle assemblies by examining the sound waves generated within the vehicle's suspension system. This approach is grounded in acoustic and mechanical principles initially explored in materials science and structural engineering.By applying this method, it is possible to determine the condition and assess the serviceability of the vehicle’s bridge structures. The implementation of such advanced and effective diagnostic tools in the automotive industry plays a significant role in enhancing vehicle reliability and preventing mechanical failures. The method also offers prospects for real-time, in-service monitoring using modern acoustic sensors and spectral analysis techniques.
Keywords: Suspension system; moving joint assemblies; typical units; structural integrity; wave propagation amplitude; spectroscopy; sonic measurements; analytical data; acoustic sensors.